ROLE OF CONDITIONALLY PATHOGENIC MICROFLORA IN HUMAN LIFE ACTIVITIES - Umarova T. A.; Kudratova Z. E.; Axmadova P. (Web of Journals Publishing, 2024)
Since the establishment of microbiology as a science, scientists have focused their attention on the study of pathogens of infectious diseases (morphology, cultivation methods, enzymatic properties, clarification of the range of susceptible organisms, pathogenesis of diseases caused by the pathogen, methods of diagnosis, treatment and prevention).
Keywords: pathogens, diagnosis, treatment, prevention, microorganisms.